Investigation of parasite and diseases at cage culture Nile tilapia (Oreochromis niloticus) in Southern region of Bangladesh - Doulah, Mohammad Ashaf Ud; Islam, SM Majharul; Rahman, Mohammad Shadiqur; Islam, Md Shariful; Rashid, Mohammad Harun or; Razzak, Mohammad Abdur (Research in Agriculture Livestock and Fisheries, 2020)
The study was carried out to identify the parasite and causative diseases on cage reared tilapia at Bakerganj upazila, Barisal district. The infected tilapia fishes were collected from the cages and brought to the laboratory to find out signs, symptoms and infection area on the fish body. Physico-chemical parameters of water, such as water temperature, pH, dissolved oxygen, nitrate, phosphate and ammonia were monitored fortnightly. The values of water temperature (°C), pH, dissolved oxygen (mg/l), nitrate (mg/l), phosphate (mg/l) and ammonia (mg/l) were 32.4±2.1, 6.2±0.3, 7.52±0.4, 0.028±.008, 11.30±2.26 and 0.09±0.02, respectively but the concentration of nitrate was so higher during the study time. Eleven species of parasites namely, Chilodonella sp, Trichodiniasp., Gyrodactylussp.,Cichlidogyrus sp., Capillariasp, Orientocreadium sp, Eustrongylidae sp, Allocreadium sp, Euclinostomum sp, Tylodelphys sp. and Metagonimus spwere were identified. Parasites were found on all the examined parts of the fish body but gill showed the most infested area of the host. Highest mortality rate was occurred in the month of October and lowest mortality rate was in July. In this circumstance, proper management system and handling are best ways to prevent diseases and reduce the mortality rate of tilapia on cage farming in the southern area. Res. Agric., Livest. Fish.6(3): 431-437, December 2019